Rational Design of Holey 2D Nonlayered Transition Metal Carbide/Nitride Heterostructure Nanosheets for Highly Efficient Water Oxidation. Issue 16 (4th March 2019) - Kou, Zongkui; Wang, Tingting; Gu, Qilin; Xiong, Mo; Zheng, Lirong; Li, Xin; Pan, Zhenghui; Chen, Hao; Verpoort, Francis; Cheetham, Anthony K.; Mu, Shichun; Wang, John
Abstract: Due to integrated advantages in electrochemical functionalities for energy conversion, 2D nonlayered heterostructure nanosheets offer new and fascinating opportunities for electrocatalysis but their fabrication is challenging when compared with the widely studied 2D layered heterostructure. Herein, a bottom‐up approach is established for facile synthesis of holey 2D transition metal carbide/nitride heterostructure nanosheets (h‐TMCN) with regulated hole sizes by controlled thermal annealing of the Mo/Zn bimetallic imidazolate frameworks (Mo/Zn BIFs). Ex situ phase and structural identifications disclose that the Mo/Zn BIFs precursor experiences interconnected three steps of transformation to produce h‐TMCN. Especially, the slow successive solid‐state diffusion of nitrogen and carbon into immediate noncrystalline molybdenum oxides allows the intergrowth of Mo2 C and Mo2 N into the 2D nonlayered heterostructure. X‐ray fine structure analysis coupled with high resolution X‐ray photoelectron spectroscopy demonstrate that Mo2 C and Mo2 N in the microdomains can chemically bond with each other, producing the abundant active N–Mo–C interfaces toward water splitting. Consequently, h‐TMCN affords low overpotentials, high turnover frequencies, rapid charge transfer, and superior long‐term stability toward electrocatalytic water oxidation. The present work demonstrates the feasibility of developing a broad range of 2D nonlayered heterostructures for high efficiency chemical energy conversion. Abstract : Holey 2D nonlayered transition metal carbide/nitride heterostructure (h‐TMCN) nanoflakes are first synthesized by a facile bottom‐up method, which enables easy regulation of hole size and thickness of sheets. The three‐step transformation mechanism is established by a series of ex situ characterization techniques. The as obtained h‐TMCN is demonstrated to be a superior catalyst toward water oxidation.